Accounting conservatism and relational contracting - Glover, Jonathan; Xue, Hao (Journal of Accounting and Economics, 2023)
This paper develops a positive role for accounting conservatism in fostering relational contracts between two agents in a two-period model of moral hazard. Building on Kreps (1996), the principal in our model designs a conservative measurement system and optimal contracts to create multiple equilibria that foster a team-based corporate culture. Accruals introduced by conservatism increase each agent's stake in the future of the relationship when it matters most—when it is going badly. This makes staying in the relationship worthwhile for the agents, even if they plan to play a low payoff equilibrium in the second period to punish first-period free-riding. In turn, this allows the principal to use lower-powered (and less costly) team incentives in the first period of the relationship. In contrast, deferred compensation increases each agent's stake in the future of the relationship when it is going well, making it less efficient in fostering relationships.